K-Pop's popularity strategy in the international arena - Ayu Nur Aini; Muhammad Fahmi; Andri Ardhiyansyah; Bagja Rahma Putra (Nusantara Science and Technology Proceedings, 2020)
This study aims to identify the successful strategy of K-pop music so that it can enter the global market from talent search to marketing. This study uses the literature review method, in this study we find that the success of the K-pop industry is the result of the strategy. such as in developing the talent of a girl band or boyband candidate using the “idol farm system” system, then using offline and online promotions. besides that the agency implemented and learned about the 4.0 marketing system. by seeking segmentation, performs 5 stages of methods of bringing in consumers, namely being aware, interested (appeal), seeking (ask), taking action (act), and supporting (advocate). Apart from the 5 approaches, there are 4 stages in marketing music, namely introducing 4.0 consumers, then doing human-oriented marketing, then doing online and offline marketing, and engagement marketing for brand affinity. To enter the international market, K-pop already has many advantages because it already has its genres and characteristics, in K-pop music also contains modernized traditional elements.